The Strength of Kicking the Ball after Preparation Period with U15 Football Players - Jovan Gardašević; Duško Bjelica; Ivan Vasiljević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
The main aim of the research was to identify a level of quantitative changes of the strength of kicking the ball with fifteen years old football players under the influence of the programmed football training of a six weeks' preparation period. The training programme covered forty-four training units. The research was made on a sample of 120 cadet level football players. To estimate the strength of kicking the ball three tests have been used: the strength of kicking the ball with foot, ball on the ground, the strength of kicking the ball with foot, ball in the air, the strength of kicking the ball with head. In the area of comparative statistics, we used discriminant parametric procedure t-test for big paired samples. It can be concluded that there are statistically significant differences in all three variables to estimate the strength of kicking the ball. This confirmed the hypothesis that the expected significant positive quantitative changes of situational-motor abilities influenced by the proposed model of training in preparation period with fifteen years old football players. The authors were guided by the fact that this kind of training program in preparation period is very effective in terms of raising the strength of kicking the ball level with fifteen years old. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population.